2019
DOI: 10.1149/2.0191910jes
|View full text |Cite
|
Sign up to set email alerts
|

Correlating the Short-Time Current Response of a Hydrogen Evolving Nickel Electrode to Bubble Growth

Abstract: Gas evolving electrochemical reactions induce bubble formation and growth at surfaces of electrodes. To study one such situation, hydrogen evolution on nickel electrodes, short time chronoamperometric experiments were performed in combination with in-situ microscopy. The entire electrode of 3.14 mm 2 was imaged with confocal microscopy and the current response of the electrode then correlated to the observed bubble growth features. Somehow counterintuitively, first a 2-3% increase in current was observed consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 29 publications
2
16
0
Order By: Relevance
“…102,130 However, when a second phase appears in the form of bubbles on or near the electrodes, they will continue to grow as the dissolved gases diffuse from the electrolyte, reducing the supersaturation of products in the electrolyte which again disturbs the equilibrium towards the products, ultimately reducing the concentration overpotential. 103,131,132,133 A recent study has shown the decoupling the concentration potential from the ohmic and activation by introducing superhydrophobic pits surrounded by a ring shaped microelectrode. Bubbles preferentially nucleated on these hydrophobic sites, preventing the masking of the electrocatalytic area and in consequence removing completely their effect on the kinetic overpotential and significantly the ohmic overpotential.…”
Section: Bubble Effects On Concentration Overpotentialmentioning
confidence: 99%
“…102,130 However, when a second phase appears in the form of bubbles on or near the electrodes, they will continue to grow as the dissolved gases diffuse from the electrolyte, reducing the supersaturation of products in the electrolyte which again disturbs the equilibrium towards the products, ultimately reducing the concentration overpotential. 103,131,132,133 A recent study has shown the decoupling the concentration potential from the ohmic and activation by introducing superhydrophobic pits surrounded by a ring shaped microelectrode. Bubbles preferentially nucleated on these hydrophobic sites, preventing the masking of the electrocatalytic area and in consequence removing completely their effect on the kinetic overpotential and significantly the ohmic overpotential.…”
Section: Bubble Effects On Concentration Overpotentialmentioning
confidence: 99%
“…The main advantage of such a configuration is that the ring electrode does not suffer from any ohmic penalties associated with bubble coverage [9], nor from the large fluctuations in the surface overpotential that usually coexist with them. For instance, bubbles detaching from microelectrodes have been reported to induce prominent positive current peaks under potentiostatic conditions [10,11], or negative peaks in the overpotential under galvanostatic conditions [12].…”
Section: Introductionmentioning
confidence: 99%
“…Note that Γ scales precisely as the inverse of the fractional concentration change defined in (15), a quantity which ideally must be kept small to ensure EΩ remains small. A value of Γ = 0.002 was used to model our experiments; Figure 7 represents the steady-state electric potential field obtained by numerically solving the steady-state Nernst-Planck equation (9) as explained in the Supplementary Information. At this low value of Γ , the obstruction due to the mere presence of the bubble can have a remarkable impact on the ohmic overpotential.…”
Section: Ohmic Overpotentialmentioning
confidence: 99%